An Overview of the Consumption Patterns and Nutritional Status of PLWHA at Karitas Hospital Weetobula - Ama, Marselino Ifantri Yuranus; Manurung, Imelda F.E.; Toy, Sarci Magdalena (Faculty of Public Health, Nusa Cendana University, 2023)
Human Immunodeficiency Virus (HIV) is a virus that attacks the immune system, causing a decrease in the patient's immune system. Karitas is a hospital located in Southwest Sumba and the number of patients undergoing ARV therapy at the hospital from 2019 to date is 40 patients. The general purpose of this study was to describe the consumption patterns and nutritional status of people living with HIV and AIDS (PLWHA) who were taking ARV therapy at the hospital. Weetobula Caritas in 2021. This type of research is descriptive with a cross sectional approach. This research was conducted in Southwest Sumba Regency in October-December 2021. The sample of this study was 40 respondents who were sampled using total sampling. The results showed that more respondents in the age group 26-45 years (85.0%), more education in the low category (55.0%), more work that did not work (80.0%), consumption patterns were more many have poor consumption patterns (60.0%), and more nutritional status in the bad category (57.5%). It is recommended for people with HIV and AIDS to adhere to ARV therapy and consume foods that contain balanced nutrition.